Effect of Food Safety Management Practices on Milk Quality and Subclinical Mastitis in Dairy Cow Farms - Tawfik, Eman Maher; Elsherbini, Mohammed; Kasem, Nahed Gomaa; Ahmed, Marwa Fawzy ElMetwaly; Abdelkhalek, Adel (Journal of Advanced Veterinary Research, 2022)
The study aimed to investigate the effect of management practices based on the principles of hazard analysis critical control points system application in dairy farms on bulk milk tank quality and the subclinical mastitis prevalence. The study was conducted on two dairy farms located in Dakahlia Governorate, Egypt using observation and questionnaire. Furthermore, cow hygiene scoring, subclinical mastitis prevalence using California Mastitis Testing, and electrical conductivity were evaluated. In addition, the organoleptic, chemical, and microbiological quality of bulk milk tanks were assessed. The results showed that farm I had better adoption of farm management practices (66.19%) than farm II (33.80%). The mean of udder and leg hygiene scores for cows showed no significant variation between both farms. The prevalence of subclinical mastitis in farm I was 0% (0/108), while it reached 6.25% (6/96) in farm II. No evidence of any abnormality during organoleptic examination on both farms. Referring to the chemical analyses, there was a higher significant difference between protein and SNF (p<0.05) in farm I than in farm II. However, this was not the case for fat, in which farm II showed a higher significance (p<0.05). Furthermore, farm I showed a significantly lower (p<0.05) somatic cell count. On the other hand, the total bacterial count (TBC), titratable acidity, and pH had no significant difference in both farms. Finally, these ensure the importance of hygiene management practices for udder health and milk quality.